Analisis Manajemen Arsip Dinamis Dinas Perpustakaan dan Arsip Kota Bandung - Arlla Yesifa, Maharani; Sukaesih, Sukaesih; Kusnandar, Kusnandar (Universitas Sebelas Maret Library, 2023)
Archives are a collection of documents that contain information and have useful value for a certain period of time. Every information institution, especially in the archives sector, needs to have archive management, including recording, storage, maintenance and depreciation. The Bandung City Library and Archives Service as an information institution should have good archive management. Therefore, researchers are interested in conducting this research to find out how archives are managed and the obstacles experienced by the Bandung City Library and Archives Service. This research uses descriptive qualitative research methods and data collection methods through observation, interviews and documentation techniques. The research conclusion is that archive management at the Bandung City Library and Archives Service is in accordance with Law Number 49 of 2009 concerning archives, starting from creation, storage, maintenance and depreciation. However, in its management the Library and Archives Service still has obstacles, such as a lack of human resources and a lack of infrastructure in the form of space to accommodate archives.